Adsorption of Malachite Green Dye by Acid Activated Carbon - Kinetic, Thermodynamic and Equilibrium Studies - P. K. Baskaran; B. R. Venkatraman; S. Arivoli (E-Journal of Chemistry)
The ability of zea mays dust carbon to remove malachite green from aqueous solutions has been studied for different adsorbate concentrations by varying the amount of adsorbent, temperature, pH and shaking time. Thermodynamic parameters such as ΔH°,ΔS° and ΔG°, were calculated from the slope and intercept of the linear plots. Analysis of adsorption results obtained at 303, 313, 323 and 333 K showed that the adsorption pattern on zea mays dust carbon seems to follow the Langmuir and Freundlich. The numerical values of sorption free energy indicate physical adsorption. The kinetic data indicated an intra-particle diffusion process with sorption being first order. The concentration of malachite green oxalate was measured before and after adsorption by using UV-visible spectrophotometer.